Taphonomy of biosignatures in carbonate nodules from the Mars-analog Qaidam Basin: constraints from microscopic, spectroscopic, and geochemical analyses - Chen, Yan; Yin, Zongjun; Lin, Wei (Frontiers in Astronomy and Space Sciences, 2024)
Early diagenetic nodules with low permeable and weather-resistant structures are considered to be favorable for biosignature preservation. Numerous nodular structures forming in neutral-to-alkaline and saline diagenetic fluids were previously identified at Gale Crater on Mars, yet their astrobiological significance remains poorly understood. In the Mars-like western Qaidam Basin, China, there are a multitude of carbonate nodules which can be analogous to those found at Gale Crater on Mars in terms of their formation backgrounds and post-depositional processes. In this study, we combine microscopic, spectroscopic, and geochemical methods to characterize the biosignature preservation of the Qaidam nodules. Carbonaceous materials, including an organic annulus inferred to be a fossil spore or algal filament microfossil, are observed in the Qaidam nodules. The total organic carbon contents of the Qaidam nodules are slightly higher than those of the surrounding fluvio-lacustrine deposits, suggesting that early diagenesis of the Qaidam nodules might facilitate the rapid entombment of biomass within magnesium carbonate or aragonite matrixes before complete degradation. The carbonate matrix showing alternating micritic and sparry layers as well as enrichment of 13C could have a physicochemical origin though the possibilities of biomineralization and organomineralization cannot be entirely ruled out. The I-1350/1600 distribution of carbonaceous materials implies the existence of carbon precursors of various subcellular components or coexisting organisms in pore waters. Organic carbon isotopes indicate the carbon fixation pathways such as the Calvin cycle or the Wood-Ljungdahl pathway utilized by organisms in pore waters. The findings of this study shed light into the taphonomy and detection of biosignatures in terrestrial playa nodules, with potential applications for biosignature exploration on Mars.